2016
DOI: 10.1371/journal.pone.0166769
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity and Structure Analysis of Percocypris pingi (Cypriniformes: Cyprinidae): Implications for Conservation and Hatchery Release in the Yalong River

Abstract: Percocypris pingi is a near threatened cyprinid species, which has suffered a dramatic decline due to anthropogenic factors. As one response to this decline, hatchery release for P. pingi has been conducted in the lower reaches of the Yalong River since 2012. To understand the conservation status of this species and the potential impact of the release of hatchery-reared fish, we studied the genetic diversity and population structure of wild and hatchery populations of P. pingi. Two hatchery populations (Jinpin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…Some previous studies have reported some adverse genetic effects caused by releasing hatchery-produced individuals in restocking programs (Cheng et al, 2011;Li et al, 2016). Here, despite the high level of heterozygosity, the wild populations of R. kutum showed lower level of allelic diversity and a sign of genetic bottleneck.…”
Section: Conclusion and Management Implicationsmentioning
confidence: 65%
“…Some previous studies have reported some adverse genetic effects caused by releasing hatchery-produced individuals in restocking programs (Cheng et al, 2011;Li et al, 2016). Here, despite the high level of heterozygosity, the wild populations of R. kutum showed lower level of allelic diversity and a sign of genetic bottleneck.…”
Section: Conclusion and Management Implicationsmentioning
confidence: 65%
“…A reduction in the number of unique alleles was also observed in the hatchery samples. Genetic diversity reduction in fish hatchery populations has been previously demonstrated (Li et al 2016;Wenne et al 2016). Selection, breeding with limited number of parents and consequently inbreeding depression appeared to be the main explanations for the decrease in genetic diversity of hatchery populations (Li et al 2016).…”
Section: Discussionmentioning
confidence: 84%
“…Genetic diversity reduction in fish hatchery populations has been previously demonstrated (Li et al 2016;Wenne et al 2016). Selection, breeding with limited number of parents and consequently inbreeding depression appeared to be the main explanations for the decrease in genetic diversity of hatchery populations (Li et al 2016). Tessier et al (1997) also reported high genetic drift and 50% reduction of effective population size in hatchery populations of Atlantic salmon due to the very small number of parents used for establishing hatchery population.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations